A bibliometric review of innovative behavior in education, 1980-2023 - Turan, Cihat; Demirtas, Zulfu; Alanoglu, Muslim (Routledge Journals, Taylor & Francis Ltd, 2025)
The research aims to examine the landscape of studies concerning innovative behavior in educational settings through a bibliometric analysis, focusing on identifying major themes, influential research, and knowledge dissemination patterns over the period from 1980 to 2023. The study employed bibliometric analysis tools including VOSviewer and R's bibliometrix package to analyze 221 studies indexed in the Scopus database. This approach allowed for mapping the network of citations, co-authorship, and keyword occurrences, providing a comprehensive overview of the field's intellectual structure. Findings indicate a growing body of literature with significant contributions from various countries, with the Netherlands, the USA, and the UK leading in citations. Analysis showed increasing research collaboration and thematic evolution from basic educational innovations to complex interdisciplinary studies involving psychological empowerment and transformational leadership. The research highlighted the increasing complexity and connectivity of studies over time, underscoring the evolving nature of innovative behaviors in educational institutions. It also identified key gaps in the literature, particularly in the integration of new pedagogical technologies and methods. The results emphasize the need for continued exploration of how innovative behaviors can be fostered in educational settings to adapt to ongoing changes in educational demands and technologies.
Keywords: teaching innovation; innovative behavior; educational innovations; creativity in education